ANALISIS PENGENDALIAN FAKTOR RESIKO DAN VEKTOR KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KELURAHAN BESAR KECAMATAN MEDAN LABUHAN KOTA MEDAN TAHUN 2022 - NURUL RAHMAH SIREGAR; LAILATUL MARDHIYAH; AFNIDAR DAULAY; MIA AFRIYANTI HARAHAP; DEWI KARTIKA; RANA LOLO KARINA (LP2MTBM MAKARIOZ, 2022)
Dengue Hemorrhagic Fever or DBD really needs to be known by the public, where th is disease is an infectious disease that can cause death. The causes of this disease really need to be known so that people are able to do prevention. Therefore, th is article will analyze the causes of dengue hemorrhagic fever, especially in Bandar Klippa Village, Percut Sei Tuan District. The method used in this study is a qualitative descriptive method. The results of interviews and observations obtained are that the causes of dengue fever in Bandar Klippa Village are the lack of environmental cleanliness, imbalance of humidity, and the position of houses that are too close together. Then, prevention and control that can be done is to get used to living clean and healthy.